Pola Asuh Orang Tua dengan Sikap Remaja tentang Seks Pranikah - Siti Mulidah; Hartati Hartati; Sunaryo Sunaryo (Jurnal LINK, 2015)
Sex education is better given by parents, rather than the child got it from own opinion or delusion. It means the parent should provide extra time to pay attention for their teen ager especially the sexual behavior. Objctive of this study to know the correlation of parents parenting with teenage attitude of premarital sex in MAN I Purwokerto Banyumas. This research design was correlation analytic with cross sectional approach. The population in this study was all of the grade X–XI students in MAN I Purwokerto as much as 769. The amount of sample in this study were 50 respondents. The research instrument used the questioner. The data analysis used deskriptif and chi-square test. The majority parenting was applied by the parents was 40% democratic parenting, and the majority teenage attitude about premarital sex was 72% nonpermissive. There was a correlation between parents parenting with teenage attitudes about premarital sex (ρ=0,001).